Synthesis, physical and chemical properties of 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetic acids salts - А.А. Safonov; О. І. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2017)
Thanks to the rapid development of science, humanity has achieved remarkable success in various fields. This also applies to the synthesis of biological compounds. Over the centuries, scientists have invented many methods and drugs that are being actively used to date. Derivatives of 1,2,4-triazole can be the foundation for the manufacture of new native drugs that will compete with foreign ones. The aim of work was synthesis and confirmation the structure of 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate acids salts. Materials and methods. As starting substances we used 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetic acids, which were synthesized by previously described methods. The structure of synthesized compounds was confirmed by the complex use of modern physical-chemical methods of analysis: elemental analysis, 1H-NMR spectroscopy, HPLC-MS. Results. Salts of 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetic acids were synthesized by the interaction of the appropriate acids with organic (morpholin, methanamin, 2-hydroxyethanamin), inorganic basics (aqueous ammonia solution, sodium hydroxide) and salts (zinc sulfate, ferrum (III) chloride, magnesium sulfate, copper (II) sulfate) in alcoholic or aqueous media. Conclusions. A series of novel 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetic acids salts were synthesized. The structure of synthesized compounds is established using modern physical-chemical methods of analysis.